ANALISIS SEMIOTIKA MAKNA PESAN “KEBEBASAN MANUSIA” DALAM APLIKASI IKLAN JUAL BELI ONLINE TOKOPEDIA - Kurniawati , Dewi; Zelfia, Zelfia; Rabiah , Sitti (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2022)
Tokopedia with the official name PT Tokopedia is a startup in the field of electronic commerce that was founded on February 6, 2009 and officially launched to the public on August 17, 2009. Has a vision to build a Super Ecosystem where anyone can start and find anything and has a mission to achieve economic equality digital. In this study, the author uses a qualitative descriptive research methodology with a semiotic analysis approach. As a descriptive study, this research only describes the situation or discourse, does not look for relationships, does not test hypotheses or make predictions. The data in this study is qualitative data (data that is without numbers or numbers), so the data are substantive categories which are then interpreted. Based on the results of research on the concept of freedom in the Tokopedia advertisement version of human freedom, #Celebrate Your Freedom is identical with seeing humans as having independence and freedom in determining their life journey. Tokopedia presents another side of freedom that you can find in each of its services. No exception when we dare to dream, free when we are not afraid to take steps to create opportunities. With the same spirit, Tokopedia was born to help as many people as possible to freely create opportunities without having to be afraid of limitations, whatever they may be.